Approaching a triumphal span: How far is China towards its Lewisian turning point? - Fang Cai (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
With the aid of an analytical framework of the Lewis model revised to reflect the experience of China, this paper examines the country's dualistic economic development and its unique characteristics. The paper outlines the major effects of China's growth as achieved during the course of economic reform and the opening-up of the country: the exploitation of the demographic dividend, the realization of comparative advantage, the improvement of total factor productivity, and participation in economic globalization. By predicting the long-term relationship between the labour force demand and supply, the paper reviews the approaching turning point in China's economic development and examines a host of challenges facing the country in sustaining growth.
Keywords: J11; J21; O53; 330; demographic dividend; Lewisian turning point; economic development; China; Dualökonomie; Demographischer Übergang; China